Diversity, enumeration, and isolation of Arcobacter spp. in the giant abalone, Haliotis gigantea. Issue 10 (5th June 2019) - Mizutani, Yukino; Iehata, Shunpei; Mori, Tetsushi; Oh, Ryota; Fukuzaki, Satoshi; Tanaka, Reiji
Abstract: Arcobacter have been frequently detected in and isolated from bivalves, but there is very little information on the genus Arcobacter in the abalone, an important fishery resource. This study aimed to investigate the genetic diversity and abundance of bacteria from the genus Arcobacter in the Japanese giant abalone, Haliotis gigantea, using molecular methods such as Arcobacter ‐specific clone libraries and fluorescence in situ hybridization (FISH). Furthermore, we attempted to isolate the Arcobacter species detected. Twelve genotypes of clones were obtained from Arcobacter ‐specific clone libraries. These sequences are not classified with any other known Arcobacter species including pathogenic Arcobacter spp., A. butzleri, A. skirrowii, and A . cryaerophilus, commonly isolated or detected from bivalves. From the FISH analysis, we observed that ARC94F‐positive cells, presumed to be Arcobacter, accounted for 6.96 ± 0.72% of all EUB338‐positive cells. In the culture method, three genotypes of Arcobacter were isolated from abalones. One genotype had a similarity of 99.2%–100.0% to the 16S rRNA gene of Arcobacter marinus, while the others showed only 93.3%–94.3% similarity to other Arcobacter species. These data indicate that abalones carry Arcobacter as a common bacterial genus which includes uncultured species. Abstract : Diversity of marine Arcobacter associated with the giant abalone Haliotis gigantea